1999
DOI: 10.1002/(sici)1099-1581(199903)10:3<151::aid-pat855>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Thermo- and pH-sensitive amphiphilic gels of copolymers of vinyl ether of ethylene glycol

Abstract: Novel thermo‐sensitive linear and crosslinked copolymers of vinyl ether of ethylene‐glycol and vinyl butyl ether have been synthesized by gamma‐irradiation copolymerization. The effect of comonomer hydrophobicity, neutral salts addition and nature of cations and anions on the position of lower critical soluble temperature of water‐soluble copolymers and swelling‐deswelling behavior of networks is demonstrated. The combination of thermosensitivity and pH sensitivity of hydrogels are realized in the case of cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…It is clearly seen that the pure monomer HEA was converted into homopolymer very fast and 80% conversion was achieved after approximately 60–70 min. An addition of VBE into the feed mixture, however, significantly reduced the copolymerization rate, which was likely due to low activity of this monomer in reactions of radical polymerization 25–27…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clearly seen that the pure monomer HEA was converted into homopolymer very fast and 80% conversion was achieved after approximately 60–70 min. An addition of VBE into the feed mixture, however, significantly reduced the copolymerization rate, which was likely due to low activity of this monomer in reactions of radical polymerization 25–27…”
Section: Resultsmentioning
confidence: 99%
“…The resulting polymers should have a proper hydrophobic–hydrophilic balance and also exhibit temperature‐induced phase separation. This possibility was demonstrated in our previous work, where thermosensitive polymers were synthesized by radiation‐induced copolymerization of vinyl ether of ethyleneglycol with vinyl alkyl ethers 25–27…”
Section: Introductionmentioning
confidence: 86%
“…All these gels showed a decrease in swelling degree as the temperature increased and exhibited volume phase transitions, although in a rather broad temperature range. A broad volume transition was also described for PEO‐PNIPAM , PEtOx‐PHEMA, PEtOx‐PHPA and poly(vinyl ether) thermoresponsive hydrogels . It was observed that the sharpness of transition is dependent upon the composition of the copolymer precursor.…”
Section: Resultsmentioning
confidence: 87%
“…The work [1] outlines a strategy for the development of artificial intelligence systems in the Republic of Kazakhstan. A distinction of this strategy lies in the integrated interdisciplinary approach to the creation of all components of artificial intelligence systems (AI), focused on a wide range of practical applications, including the creation of molecular informatics systems [2,3] based on the latest achievements in the field of physical chemistry of polymers [4,5]. As is known, one of the most important areas of AI systems development is artificial neural networks (ANNs).…”
Section: To the Question Of Physical Implementation Of Optical Neuralmentioning
confidence: 99%